Assessment and treatment of muscle imbalance. The Janda approach. - Page, P.; Frank, C.; Lardner, R. (Human Kinetics, 2010)
Assessment and Treatment of Muscle Imbalance: The Janda Approach blends postural techniques, neurology, and functional capabilities in order to alleviate chronic musculoskeletal pain and promote greater functionality. Developed by Vladimir Janda, respected neurologist and physiotherapist, the Janda approach presents a unique perspective to rehabilitation. In contrast to a more traditional structural view, the Janda approach is functional - emphasizing the importance of the sensorimotor system in controlling movement and chronic musculoskeletal pain syndromes from sports and general activities. Assessment and Treatment of Muscle Imbalance: The Janda Approach is the only text to offer practical, evidence-based application of Janda`s theories.